Exploring the embodied narrations of the city - Suvi Satama; Juulia Räikkönen (Emerald Publishing, 2022)
This study aims to explore how people bodily narrate and use collective memory to clarify their embodied experiences regarding a city which they memorise. Drawing on 1,359 short stories collected by the online travel portal Visit Turku about ‘How the city feels’, the fine-grained embodied experiences of people are represented through descriptions of their feelings towards the city of Turku. Based on the analysis, two aspects through which the respondents narrated their embodied experiences of cities have been identified: (1) the sociomaterial entanglements with the city and (2) the humane relationship with the city. This study is limited to short stories acquired online, raising questions of anonymity and representativeness. Thus, these narrations are constructions which have to be interpreted as told by specific people in a certain time and place. Tourist agencies should pay attention to the value of looking at written stories as bodily materialisations of people’s experiences of city destinations. Understanding this would strengthen the cities’ competitiveness.  By empirically highlighting how people memorise a city through narrations, the study offers novel viewpoints on the embodied experiences in cities as well as the cultural constructs these narrations are based on, thus broadening our understanding of how cities become bodily entangled with us.